Collection Condition Assessment in a Midsized Academic Library. Issue 4 (1st October 2016) - Rinio, Tyson
ABSTRACT: In 2014, Rasmuson Library at the University of Alaska Fairbanks conducted its first collection condition survey. The institutionally significant Alaska Collection was chosen as a manageable project. Research design based on the literature review led the researcher to conduct two surveys: one examining the entire collection and one looking at only those books most recently circulated. The combined surveys revealed that the circulating books are much more badly damaged that the books in the collection that do not circulate, across a variety of attributes.